CHAUCER’S THE CANTERBURY TALES: A REFLECTION OF MEDIEVAL SOCIETY (Ustozlar uchun, 2025)
One of the most important pieces of medieval English literature is Geoffrey Chaucer's The Canterbury Tales, which provides a rich and complex depiction of society in the fourteenth century.  The narrative depicts social hierarchies, economic shifts, religious corruption, gender interactions, and changing values of the late Middle Ages through its varied cast of travelers.  Chaucer is both a literary classic and a significant historical record because of his realism and sarcasm, which highlight the virtues and vices of medieval life.